(untitled) (Texas Journal of Medical Science, 2023)
The authors pay special attention to the fact that in chronic purulent epitympanitis, bone tissue is involved in the inflammatory process, and a chronic purulent-destructive change occurs in the cells of the mastoid process. Osteomyelitis of the bones leads to local and intracranial complications. Therefore, during sanitizing operations of the middle ear in epitympanitis, it is necessary to radically remove all foci of destructively altered structures of the middle ear system with exposure of the dura mater of the middle and posterior cranial fossae. Postoperative management of patients should be directed to intensive care.